2014
DOI: 10.1016/j.juro.2014.02.043
|View full text |Cite
|
Sign up to set email alerts
|

The Dramatic Increase in Social Media in Urology

Abstract: Twitter has emerged as a significant communication platform at urological meetings. Use increased dramatically between 2012 and 2013. Urologists have increasingly led this discussion with an increased focus on data arising from meeting proceedings. This adjunct to traditional meeting activity merits the attention of urologists and the professional associations that host such meetings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 5 publications
0
75
0
6
Order By: Relevance
“…2 SoMe offers healthcare professionals novel avenues to teach, learn, and care. [3][4][5][6][7] Within urology, SoMe is used to conduct an international e-journal club, 8 facilitate open-access discussions at conferences, 9,10 disseminate information from prominent journals and societies, 11 identify areas for improvement in educational resource distribution to patients, [12][13][14] rapidly and accurately assess robotic surgical suturing performance, 15 network professionally, 16 and improve response rates to surveys. 16 Due to the bourgeoning connection between SoMe and urology, a standardized nomenclature to discuss urologic topics online has been created.…”
Section: Introductionmentioning
confidence: 99%
“…2 SoMe offers healthcare professionals novel avenues to teach, learn, and care. [3][4][5][6][7] Within urology, SoMe is used to conduct an international e-journal club, 8 facilitate open-access discussions at conferences, 9,10 disseminate information from prominent journals and societies, 11 identify areas for improvement in educational resource distribution to patients, [12][13][14] rapidly and accurately assess robotic surgical suturing performance, 15 network professionally, 16 and improve response rates to surveys. 16 Due to the bourgeoning connection between SoMe and urology, a standardized nomenclature to discuss urologic topics online has been created.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One of the major uses is advocacy and policy discussion. For example, following the U. S. Preventive Services Task Force recommendation, there was a robust Twitter reaction (5357 tweets).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three years, Twitter has evolved as an important communication platform at conferences with steadily growing participation, 3 which led to the recent record of 12 857 tweets during the 2015 American Urological Association (AUA) conference. 6 Numerous studies have reported increasing use of Twitter at urologic conferences 3,4,[7][8][9] and urologists were the main contributors to the Twitter discussions. 4,7 A recent content analysis from a global endourology conference showed that 57% of tweets were related to the scientific content of the meeting.…”
Section: Introductionmentioning
confidence: 99%
“…Cirugía (17,18) ; Radiología (19) ; Promoción de la salud (20) ; Farmacología (21) o Urología (22,23) , por mencionar algunos ámbitos sanitarios.…”
Section: Enfermería Globalunclassified